2012
DOI: 10.1200/jco.2010.30.3404
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cardiac Biomarkers During Doxorubicin Treatment of Pediatric Patients With High-Risk Acute Lymphoblastic Leukemia: Associations With Long-Term Echocardiographic Outcomes

Abstract: A B S T R A C T PurposeDoxorubicin causes cardiac injury and cardiomyopathy in children with acute lymphoblastic leukemia (ALL). Measuring biomarkers during therapy might help individualize treatment by immediately identifying cardiac injury and cardiomyopathy. Patients and MethodsChildren with high-risk ALL were randomly assigned to receive doxorubicin alone (n ϭ 100; 75 analyzed) or doxorubicin with dexrazoxane (n ϭ 105; 81 analyzed). Echocardiograms and serial serum measurements of cardiac troponin T (cTnT;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
249
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(260 citation statements)
references
References 42 publications
6
249
0
5
Order By: Relevance
“…In the current study, we quantitatively compared the global proteomic profiling of rat cardiomyocyte H9c2 cells with and without doxorubicin addition at a clinical relevant concentration, which exhibited an apoptosis-inducing effect, but not significant cellular damage in H9c2 cells (6,8). Our proteomic analysis revealed a series of proteins varied in cardiomyocytes after doxorubicin treatment for 48 h, in which 10 differentially regulated proteins were enriched in the biological process of apoptosis, which have been…”
Section: Western-blotmentioning
confidence: 92%
“…In the current study, we quantitatively compared the global proteomic profiling of rat cardiomyocyte H9c2 cells with and without doxorubicin addition at a clinical relevant concentration, which exhibited an apoptosis-inducing effect, but not significant cellular damage in H9c2 cells (6,8). Our proteomic analysis revealed a series of proteins varied in cardiomyocytes after doxorubicin treatment for 48 h, in which 10 differentially regulated proteins were enriched in the biological process of apoptosis, which have been…”
Section: Western-blotmentioning
confidence: 92%
“…This result opens a perspective to regular monitoring of hs-CRP level for identifying women with early-stage breast cancer at low risk for asymptomatic trastuzumab-induced cardiotoxicity. In contrast, Lipshultz et al [39] did not find closely association between increased hs-CRP and any echocardiographic variables in doxorubicin-treated subjects with acute lymphoblastic leukemia, although cardiac troponin T and NTproBNP were related to an abnormal LV thickness-to-dimension ratio, suggesting LV remodeling. In general, definitive validation studies are required to fully establish clinical utility of hs-CRP in cancer patients as biomarker of cardiotoxicity.…”
Section: High-sensitivity C-reactive Proteinmentioning
confidence: 83%
“…[14][15][16][17] In addition, serum biomarkers, particularly high-sensitivity cardiac troponins and NTproBNP, may be useful in predicting the development of cardiac dysfunction. 18 Changes to the adrenergic system could potentially be involved in the development of anthracycline-induced cardiac dysfunction. Using radiotracer technology, over 20 years ago, small studies demonstrated that myocardial iodine-123 meta-iodobenzylguanidine (I-123 MIBG) uptake is decreased in patients receiving anthracyclines in a dose-dependent way.…”
Section: See Related Article Pp 256-264mentioning
confidence: 99%